Health Risks Associated With Pesticide Residues in Sediments, Fish, and Plants From the Oue´me´ Valley in the Republic of Be´nin - YEHOUENOU AZEHOUN PAZOU, ELISABETH (My University, 2013)
Abstract To determine possible human and environmental health risks, organochlorine pesticide residues were determined in vegetables grown in floodplains along the Oue´me´ River near Lowe´ in Be´nin. Testing of vegetables found 13 pesticides with RDDT, a-endosulfan, Rdrin, and lindane being most important. The same pesticides were also detected in plants eaten by bovine cattle, sheep, and herbivorous fish. Human pesticide intake by vegetable consumption was compared with tolerable daily intake (TDI) values reported by the World Health Organization. Pesticide intake by fish consumption was estimated from residue levels in whole fish collected from the Oue´me´ River in 2004 and reported earlier. Fish consumption does not pose a risk for human health, but consuming vegetables that contain pesticide residues may lead to exceedance of TDI values. Based on these findings, concerns are warranted, and more work is needed to understand the full exposure profile for the local population.
Keywords: health risks; Fish consumption